Enhancing Junior High School Students’ Numeracy Literacy Through a Competency-Based Problem-Based Learning Model: Development and Implementation - Christa Voni Roulina Sinaga; Apriani Sijabat; Elisabet Pebrina Br.Ujung; Arianto Munthe (STAI Hubbulwathan Duri, 2025)
The Minimum Competency Assessment (AKM) emphasizes the importance of numeracy literacy among students. In response, this study aims to develop a valid and practical problem-based learning (PBL) model to enhance numeracy skills in junior high school students, offering a reference framework for mathematics educators. A Research and Development (RD) methodology was employed using the 4D model: Define, Design, Develop, and Disseminate. The research involved iterative trials to evaluate and refine the effectiveness of the proposed PBL model. The developed PBL model showed high validity and practicality. Students’ mathematical numeracy achievement reached 87.50% using the classical PBL approach. Additionally, average numeracy scores improved from 2.73 in Trial I to 3.05 in Trial II. Students demonstrated active engagement throughout the learning process, meeting criteria for effective learning as defined in the study. The results confirm that the PBL model effectively enhances students’ numeracy literacy and supports active learning. The novelty of this study lies in the validated and effective instructional device developed through a structured RD process. The final model provides a practical tool for mathematics instruction in junior high schools, concluding the development cycle with promising implications for curriculum design and pedagogical practice.